EDUKASI TENTANG PERSONAL HYGIENE SAAT MENSTRUASI PADA REMAJA PUTRI - Harahap, Mustika; Ningsih, Rena Afri; SN, T Hartian; Andriani, Andriani; Mulyani, Siska (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2024)
Abstract : Adolescent Reproductive Health (ARH) is an integral part of health and family planning programs in Indonesia. Adolescents are one of the targets in reproductive health. Adolescence is a transition period from childhood to adulthood, during which many changes occur, both physical and psychological. Reproductive health is a condition where adolescents are socially, physically and spiritually healthy in relation to the reproductive system, reproductive function and reproductive roles of adolescents. The aim of this community service is to increase the knowledge of MTs Muhammadiyah 02 Pekanbaru students. Community service activities in the form of health education using power point media can be used to increase knowledge. Through this activity, it is recommended that reproductive health information continue to be conveyed to female students. This activity ran smoothly and the activity participants participated seriously and enthusiastically.